Concepts and implementation of talaqqi and musyafahah methods in learning the Quran - Najmiah, Omar; Nor Hafizi, Yusof; Nurul Huda, Zainal Abidin (2019)
Talaqqi musyafahah is a method of studying the Quran face to face where the delivery and teaching method is directly from a teacher to a student. It is a method inherited by the Prophet s.a.w from Gabriel a.s and subsequently implemented by Rasulullah s.a.w to the companions. The companions continued this pedagogy until it is inherited as a learning system of the Quran until today. The development of the educational system has featured various Quranic learning systems, including distance learning, as well as through the internet which is just a virtual learning via video in a unidirectional approach or written basis. This modern method has raised the question of how far it meets the talaqqi musyafahah system taught by the Prophet s.a.w. This study is aimed at explaining the true concept and importance of talaqqi musyafahah as well as the method of implementation in the study of the Quran. This qualitative study selected descriptive methods by collecting and analyzing the opinions of the early and current scholars through books, journals, and authoritative websites with respect to the topic of debate. The study found that talaqqi musyafahah is very important in the process of teaching the Quran because there are several words in the Quran that have different pronunciation compared to their written forms such as as the word(فم (in al-Dzariyat: 47. Also, there is a special method in Imam Hafs recitation technique such as reciting the word (ها َرا َج ْم ,(َisymam or roum for the word (اَّمنَ ْ أَت (in Yusuf: 11, and tashil baina baina recitation for the word (سج (in Fussilat: 44, which cannot be learned by only referring to their writings in the mushaf and any books of tajwid. It requires talaqqi and musyafahah from a qualified teacher. It is also important to realize the continuity of sanad which is one of the components in reciting the Quran. In conclusion, any methods of learning the Quran must conform to the talaqqi and musyafahah methods taught by Rasuluullah s.a.w.